Famesick : a memoir [compact disc, unabridged] - Dunham, Lena, 1986- (Penguin Random House, 2026)
Lena Dunham asks herself what the cost of fulfilling her dreams has really been, and whether it was worth it. What she finds is deeper than physical relief, and more lasting, as she learns to live with what she can't change and turn her regrets into wisdom that can carry her forward, as she reconnects to what, and who, she loves.